Communicative grammar in modern Ukrainian linguodidactics - Andreyeva, Tetyana (Current issues of Ukrainian linguistics: theory and practice, 2019)
This article examines the notion of communicative grammar in its relations with the Ukrainian linguodidactics. This problem is related to the language competence, which serves as a component of communicative competence. The present stage of studying the numerous problems of linguistics is characterized by the fact that they are considered in a cognitive-communicative perspective. The fact of the establishment of a cognitive-communicative paradigm in modern linguistics leads to the foreground of the study, which uses the functional description of the language system and its constructive units. Application of the communicative-activity approach corresponds most closely to modern educational goals and psycho-pedagogical ideas of the present, as it creates the preconditions for the active formation of communicative competences among students, serving as the main goal of standardized language education at all levels. The communicative approach to the study of the linguistic system demonstrates the applicable nature, because it involves mastering the linguistic material as an action: acquisition of the lexical and grammatical system of language based on their communicative importance. The specificity of modern research in the field of grammar was the emergence of various types of grammar (generative grammar, communicative grammar, functional grammar). Communicative grammar is one of the areas of language learning, which combines the systematic representation of grammar and text analysis (as part of this, there is a broad term in grammar, it also includes the lexical semantics). Significant linguistic units were in the focus of the study of communicative grammar in connection with the communicative activity of the speaker. The main object of this science is the text, and its purpose is the justification of the specific text and each of its components, the creation of an explanatory model of the grammatical system (that is the definition of functional and semantic specificity of grammatical units, the identification of functional and semantic principles that underpin the organization of the grammatical system). In our opinion, the linguo-didactic elaboration of a range of issues that lie in the sphere of interest in communicative grammar is still rather small. The development of the theory of communicative grammar itself in Ukrainian linguistics, and its linguistic and pedagogical elaboration, is, in large part, a matter of scientific and methodological perspectives.
Keywords: communicative linguistics, communicative grammar, linguodidactics, cognitive-communicative paradigm, linguistic system, pragmalinguistics, semantics, text.